Protective roles of FICZ and aryl hydrocarbon receptor axis on alveolar bone loss and inflammation in experimental periodontitis. (14th August 2019) - Huang, Jing; Cai, Xinjie; Ou, Yanjing; Fan, Le; Zhou, Yi; Wang, Yining
Abstract: Aim: The aryl hydrocarbon receptor (AhR)‐ligand axis has been shown to be involved in inflammatory diseases and bone homeostasis. However, the activation of AhR signalling pathway and the possible functions of AhR ligands in periodontitis are underexplored. This study investigated the expression of the AhR target gene cytochrome P450 subfamily B member 1 (CYP1B1) and the functions and mechanisms of the AhR ligand 6 formylindolo[3, 2‐b]carbazole (FICZ) in periodontitis. Materials and Methods: CYP1B1 expression was detected in human periodontitis samples, mice with ligature‐induced periodontitis and lipopolysaccharide (LPS)‐induced inflammation in periodontal ligament cells (PDLCs) in vitro. FICZ was administered topically or systemically. The therapeutic functions of FICZ were detected via qPCR, micro‐computed tomography and immunohistochemistry. Finally, the mechanisms of AhR signalling in periodontitis were investigated by cell assays. Results: CYP1B1 expression was downregulated in periodontitis. FICZ rescued the alveolar bone loss and mitigated the inflammatory cytokines in periodontitis mice. In vitro, FICZ pre‐treatment reduced the LPS‐induced inflammation in PDLCs via the increased phosphorylation of STAT3. Additionally, FICZ prompted the mineralization of PDLCs via activation of the Wnt/β‐catenin signalling pathway. Conclusion: AhR signalling pathway is suppressed in periodontitis and the AhR ligand FICZ can prevent periodontitis.